1998
DOI: 10.1161/01.cir.97.19.1921
|View full text |Cite
|
Sign up to set email alerts
|

Plasma N-Terminal Pro–Brain Natriuretic Peptide and Adrenomedullin

Abstract: Plasma N-BNP measured 2 to 4 days after myocardial infarction independently predicted left ventricular function and 2-year survival. Stratification of patients into low- and high-risk groups can be facilitated by plasma N-BNP or BNP measurements, and one of these could reasonably be included in the routine clinical workup of patients after myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
146
2
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 575 publications
(163 citation statements)
references
References 28 publications
10
146
2
5
Order By: Relevance
“…Other studies have demonstrated a similar pattern of risk for patients with elevated NT-proBNP (5,6,(13)(14)(15)(16)(17)(18). Our study extends these prior findings by demonstrating that, at baseline, 24 h and 72 h, NT-proBNP predicts adverse events independent Other studies have demonstrated that BNP predicts adverse events, particularly sudden cardiac death, in both the postmyocardial infarction (19) and heart failure populations (20).…”
Section: Prognosissupporting
confidence: 84%
See 1 more Smart Citation
“…Other studies have demonstrated a similar pattern of risk for patients with elevated NT-proBNP (5,6,(13)(14)(15)(16)(17)(18). Our study extends these prior findings by demonstrating that, at baseline, 24 h and 72 h, NT-proBNP predicts adverse events independent Other studies have demonstrated that BNP predicts adverse events, particularly sudden cardiac death, in both the postmyocardial infarction (19) and heart failure populations (20).…”
Section: Prognosissupporting
confidence: 84%
“…First, although we have demonstrated that NT-proBNP within the first 72 h has powerful prognostic information after an acute myocardial infarct, it is unclear whether the same relationship will be evident if NT-proBNP is assessed later. However, elevated natriuretic peptides after STEMI have consistently demonstrated a strong, negative prognostic value even up to two years (17). Second, we chose to treat NT-proBNP as a continuous variable and in quartiles rather than use a specified cutpoint as is done elsewhere (15).…”
Section: Limitationsmentioning
confidence: 99%
“…Circulating levels of the cardiac natriuretic peptides, particularly brain natriuretic peptide (BNP) and the 1-76 amino-acid N-terminal pro-BNP (NT-proBNP), have been identified as robust biochemical markers of heart failure in patients presenting with acute shortness of breath, [1][2][3][4] as prognostic indices for mortality and the development of heart failure following acute myocardial infarction, 5,6 and as potentially useful guides to the intensity of pharmacotherapy in patients with chronic heart failure. 7 Natriuretic peptide levels have been reported also to be higher in patients with hypertension, especially those with left ventricular hypertrophy or dysfunction, than in normotensive subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in nondiabetic populations have shown that plasma levels of both BNP and NTproBNP facilitate the diagnosis of heart failure. Moreover, these novel risk factors are correlated with functional status in patients with congestive heart failure [13]. Plasma levels of BNP and NT-proBNP also correlate with left ventricular dilatation, remodelling and dysfunction [13][14][15].…”
Section: Discussionmentioning
confidence: 99%